2007
DOI: 10.1177/10534512070430020701
|View full text |Cite
|
Sign up to set email alerts
|

Tutoring System Innovations

Abstract: This article discusses the progression of tutoring system innovations from informal, dyadic, and subjectively evaluated arrangements to more formally arranged configurations that emphasize training, application, and evaluation. Suggestions for future innovations, based on existing prototypes, are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
2
0
2
Order By: Relevance
“…Згідно з напрацьованими організаційно-методичними матеріалами, такі функції тьютора мають здійснюватися на двох етапах. На першомупідготовчому -тьютор знайомиться з матеріалом навчального курсу, якщо він не є його автором; з'ясовує запити, інтереси, потреби, інші аспекти, що стосуються його опанування студентами; визначає принципи і методи дистанційного навчання на основі аналізу профільної літератури та участі у семінарах [8].…”
Section: інтерфейси коучингу крізь призму науково-педагогічного дискурсуunclassified
See 1 more Smart Citation
“…Згідно з напрацьованими організаційно-методичними матеріалами, такі функції тьютора мають здійснюватися на двох етапах. На першомупідготовчому -тьютор знайомиться з матеріалом навчального курсу, якщо він не є його автором; з'ясовує запити, інтереси, потреби, інші аспекти, що стосуються його опанування студентами; визначає принципи і методи дистанційного навчання на основі аналізу профільної літератури та участі у семінарах [8].…”
Section: інтерфейси коучингу крізь призму науково-педагогічного дискурсуunclassified
“…На другому етапі -під час навчального процесу -здійснює координаційні функції: складає і передає студентам розклад, процедурні вимоги проведення занять, перебуває з ними в особистому зв'язку та допомагає розв'язувати проблеми і долати труднощі, з яким вони стикаються при опануванні курсу; узгоджує з адміністрацією пов'язані з цим організаційні питання; коригує і за необхідності вдосконалює зміст навчального курсу і методику його вивчення тощо [8].…”
Section: інтерфейси коучингу крізь призму науково-педагогічного дискурсуunclassified
“…Students who participated as tutors, and tutees and then switched roles benefitted from the experience by building relationships with others as academic skills improved. Other studies (Dzubak, 2009;Gardner, 2007) credited tutoring programs with providing other social benefits and Opp (2002) concluded that colleges which provided peer tutors were more likely to have high completion rates.…”
Section: Tutoring Systems: An Evolutionmentioning
confidence: 99%
“…1: E11 Opportunities Task Force, 2002: Sheets, 2009. The literature has indicated that tutoring is useful to tutees (Dzubak, 2009;Gardner, 2007). Tutors benefit from monetary remuneration, consolidation of learning and increased social skills (Jung, Tryssenaar & Wilkins, 2005;Shelton, 1990).…”
Section: Evaluation and Next Stepsmentioning
confidence: 99%